Clinical Outcomes and Adverse Events after First-Line Treatment in Metastatic Renal Cell Carcinoma: A Systematic Review and Network Meta-Analysis. Issue 1 (21st January 2022) - Nocera, Luigi; Karakiewicz, Pierre I.; Wenzel, Mike; Tian, Zhe; Shariat, Shahrokh F.; Saad, Fred; Chun, Felix K. H.; Briganti, Alberto; Kapoor, Anil; Lalani, Aly-Khan
Abstract : Purpose: Four recent first-line clinical trials leveraging immune-oncology agents demonstrated an overall survival (OS) benefit relative to sunitinib. We aimed to provide formal comparisons among immune-oncology combinations in terms of OS, progression-free survival (PFS), objective response rates and treatment-related adverse events (AEs). Materials and Methods: PubMed® database was searched for studies indexed from January 1, 2016 through March 6, 2021. Only phase III randomized clinical trials with proven OS benefit relative to sunitinib were included: CheckMate 214 (nivolumab plus ipilimumab [N+I]), KEYNOTE-426 (pembrolizumab plus axitinib [P+A]), CheckMate 9ER (nivolumab plus cabozantinib [N+C]) and KEYNOTE-581 (lenvatinib plus permbrolizumab [L+P]). OS represented the primary outcome. PFS, objective response rate and AEs represented secondary outcomes. Results: Overall, 3, 320 patients were included. Regarding OS, N+C ranked first, followed by L+P, P+A and N+I. Regarding PFS and objective response rate, L+P ranked first, followed by N+C, P+A and N+I. Finally, N+I ranked first with respect to lowest grade 3+ AEs, followed by P+A, N+C and L+P. Differences in followup duration, risk grouping and nephrectomy rates distinguish the studies. Conclusions: N+C may provide the most favorable OS, L+P the most favorable PFS and ORRs, and N+I the lowest toxicity. Population differences may potentially undermine the generalizability and the robustness of findings of metastatic renal cell carcinoma.